CRISPR/Cas9-mediated sgRNA design targeting UDP-Glycosyltransferases (UGTs) in Indonesian local rice - MOHAMMAD UBAIDILLAH; REZA MUHAMMAD SYARIF; ANGGER AISYAH HADIAHNING GUSTI; ROSALINA DIVA AURELA; IHSAN HABIBI; SRI HARTATIK; RIKNO HARMOKO; KYUNG MIN KIM (Society for Indonesian Biodiversity, 2026)
Abstract. Ubaidillah M, Syarif RM, Gusti AIH, Aurela RD, Habibi I, Hartatik S, Harmoko R, Kim KM. 2026. CRISPR/Cas9-mediated sgRNA design targeting UDP-Glycosyltransferases (UGTs) in Indonesian local rice. Biodiversitas 27 (1): d270108. https://doi.org/10.13057/biodiv/d270108. Sakuranetin serves as a vital phytoalexin in rice and exhibits notable pharmacological properties. Its biosynthesis is catalyzed by the OsNOMT enzyme and regulated by UDP-Glycosyltransferase (UGTs) genes, which divert naringenin into other flavonoids, thereby limiting sakuranetin production. This study aimed to design and construct specific single-guide RNA (sgRNAs) targeting UDP-Glycosyl Transferase (UGTs) genes precisely via CRISPR/Cas9 to establish genetic tools for metabolic engineering. Glucosyltransferases were collected from GenBank and aligned using Clustal Omega 13. The sgRNA oligonucleotides were designed using CHOPCHOP version 3, yielding information related to PAM, sgRNA efficiency, GC content, and others. A total of three sgRNAs were produced, with two showing efficiencies that match the target gene UGTs with predicted highest on-target sites and GC content above 60%. The designed sgRNA was successfully constructed into plasmid pRGEB32 and transformed into Agrobacterium tumefaciens LBA4404. Molecular validation confirmed plasmid integrity and sgRNA insertion through PCR amplification and sequencing. Preliminary transformation trials using Indonesian local rice varieties (Merah Wangi, Pandan Wangi, and Pontianak) revealed genotype-dependent variability, with Pandan Wangi showing the highest transformation efficiency and callus survival. These results demonstrate a molecular foundation for precise metabolic pathway engineering to enhance stress-adaptive and disease-resistant traits in local rice cultivars.